FACTORS INVOLVED IN READMISSIONS FOR OLDER VETERANS RECEIVING EARLY HOMECARE. (11th November 2018) - Hornick, T; Fine-Smilovich, E; Banks, R; Knighton, S; Slivka, J; Al Battashi, H; Higgins, P
Abstract: This mixed methods study examined medical and social issues of older adults newly discharged from the hospital. Previous studies have focused primarily on medical conditions that lead to early readmission; clinicians, however, maintain that medical conditions are not the only cause of readmissions. Using the Healthy People 2020 framework of Social Determinants of Health (SDOH) we conducted a retrospective mixed methods study of 106 veterans admitted to a Home Based Primary Care Program (HBPC) after discharge from the hospital; all were diagnosed with CHF and/or COPD. Quantitative data abstracted from charts included socio-demographics, illness and utilization. Patient notes from HBPC staff were used for a qualitative analysis of SDOH, defined as social, physical, and functional factors that affect a person's health. The mean age of the mostly male sample was 78 years (range=64–94). Mean Charlson score was 6.02; 28(21.4%) were readmitted within 30 days, 65(61.3%) were readmitted in 6 months. Content analysis indicated that 39 veterans (36.7%) had SDOH noted in their progress notes. The most commonly noted issue was caregiver problems/stress in 20(18.9%), followed by environmental issues in 14(13.2%). 8(7.5%) had falls, and 2(1.9%) had active substance abuse. 42(39.6%) were mismanaging prescribed medications. Network analysis will be used to evaluate associations between the identified factors and hospital readmissions. This small study provides preliminary evidence that social factors should be considered in future models that attempt to predict early readmission in patients with COPD and/or CHF.